Phytochemical Compounds, Antioxidant, and Digestive Enzymes Inhibitory Activities of Different Fractions from Ginkgo biloba L. Nut Shells - Luo Liu; Yiyi Shang; Yan Zhang; Mingjie Pang (Journal of Food Quality)
This study was designed to investigate the phytochemical compounds, antioxidant, and digestive enzymes inhibitory activities of the free (F), esterified (E), and insoluble-bound (IB) fractions from Ginkgo biloba L. nut shells. Results showed that a total of twelve compounds were detected in G. biloba nut shells by using UHPLC-ESI-HRMS/MS, including two kinds of organic acids, three kinds of phenolic acids, three kinds of flavonoids, and four kinds of terpene lactones. The F fraction contained all identified compounds and had the highest contents of the total phenolics and total flavonoids. All of the three different fractions exhibited good DPPH radical and ABTS radical cation scavenging activities and strong inhibitory effects on the generation of intracellular reactive oxygen species (ROS). Moreover, these three fractions also had good inhibitory effects towards α-glucosidase and pancreatic lipase. Among the three fractions, the F fraction possessed the strongest bioactivities. The findings obtained in the current study may provide some insights and bases for the further investigation and application of G. biloba nut shells in clinical medicine or the nutraceutical industry.